Semiotica per campagne di digital marketing. Alcune proposte operative - Giovanna Cosenza (Ocula)
This work is part of the extensive series of semiotic studies that, from the late 1980s to the present, have dialogued with the most diverse areas of marketing, up to the most recent digital marketing. It proposes a path that is not only concerned with academic research, whether theoretical or applied, but also takes a professionalizing perspective, according to which various concepts from generative and interpretive semiotics, enunciation theory, compositional semantics, up to visual semiotics, can be functional in designing digital marketing campaigns.